2021
DOI: 10.1038/s41598-021-83321-x
|View full text |Cite
|
Sign up to set email alerts
|

-308G/A polymorphism of tumor necrosis factor alpha (TNF-α) gene and metabolic syndrome susceptibility: a meta-analysis

Abstract: Many studies tried to assess the relationship between -308G/A polymorphism of tumor necrosis factor alpha (TNF-α) gene and risk of metabolic syndrome (MS), but their results were contradictory. This meta-analysis aimed to precisely evaluate this association. A systematic literature search was performed in Pubmed database and WanFang Med Online, STATA software 14.0 was used for the meta-analysis. Eleven independent studies containing 3277 cases and 3312 controls were included in our meta-analysis. In overall an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…For identifying the risk variants that cause the disease of interest, the "candidate gene studies approach" has been at the forefront in uncovering the correlation between genetic variants with complex diseases [22]. Multiple meta-analyses and other researchers have found a relationship between TNF-α 308GandA polymorphism with variations in susceptibility to several diseases between diferent people and, on a wider scale, across diferent populations [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…For identifying the risk variants that cause the disease of interest, the "candidate gene studies approach" has been at the forefront in uncovering the correlation between genetic variants with complex diseases [22]. Multiple meta-analyses and other researchers have found a relationship between TNF-α 308GandA polymorphism with variations in susceptibility to several diseases between diferent people and, on a wider scale, across diferent populations [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review suggested that TNF-α could be an early biomarker to detect MetS [ 24 ]. Some studies have demonstrated that TNF-α gene polymorphisms were associated with the susceptibility of MetS, but the results were inconsistent in different ethnic groups [ 25 ]. Making an effort to elucidate the interactions of TNF-α genetic variants and environment was considered as a potential method to improve MetS [ 26 ].…”
Section: Introductionmentioning
confidence: 99%